Broadband Impedance Matching and Phase Shifting via Transfer Function of a Two-Port Network - ŞENGÜL, METİN (Emerald Group Publishing Ltd., 2025)
PurposeIn the literature, broadband impedance matching and phase shifting are well-known subjects, and there are many different design procedures in which several gain and phase expressions are used; for instance, transducer power gain in impedance matching problems and scattering parameter S21 in phase shifting problems. The purpose of this study is to use the same expression to design both broadband power transfer networks and phase shifter sections.Design/methodology/approachIt is seen that the best choice is to use transfer function of the two-port network, since gain and phase information can be obtained from it. But the gain defined in transfer function expression is the ratio of voltages, not the ratio of powers, therefore, a new power gain expression in terms of transfer function is derived.FindingsIn the given broadband impedance matching and phase shifting examples, transfer function of the two-port network is used to design the networks. It is concluded that the performances of the two-port networks given in the examples are very close to the performances of the two-ports obtained via the procedures defined in the literature.Originality/valueIn broadband matching problems, a transducer power gain expression is used, and in phase shifting problems, first circuit topology of phase shifter section is fixed and then component values are calculated. So, there is no unique expression capable of solving both impedance matching and phase shifting problems. Therefore, a unique expression is suggested in this paper and this gap in the literature has been filled.
Keywords: Circuits; Equalizers; Impedance Matching; Passive Networks; Phase Shifters; Transfer Functions